La desviación de poder en el proceso contencioso administrativo - Rojas Ortega, Alex (Universidad de Costa Rica - Colegio de Abogados y Abogadas de Costa Rica, 2018)
Misuse of power is a creation of the Council of State of France, and it refers to the exercise of the administrative regulatory powers, for purposes other than the ones set out in the body of laws. When Public Administrations deviate from the established regulatory purpose, they engage in a defect of legality that, therefore, must be known by the contentious-administrative jurisdiction.In our opinion, judges must give misuse of power a first order implementation, especially if we take into account that misuse of power has its basis on the supreme de-law of our legal system (Article 49 of the Constitution) which allows its progressive and extensive application, for the direct interest of the parties involved and the constitutional protection of legality of the State´s conduct in a broader sense.